Crystallization kinetics of Sn-MFI molecular sieve formation by dry gel cross mark conversion method - Niphadkar, P. S.; Tangale, N. P.; Joshi, P. N.; Awate, S. V. (Microporous and Mesoporous Materials, 2013)
The conversion of amorphous stannosilicate dry gel into crystalline molecular sieve with MFI structure (Sn-MFI) was achieved by dry gel conversion (DGC) method at 413, 443 and 473 K. For comparison purpose, Sn-MFI molecular sieve with similar SiO2/SnO2 mole ratio was also obtained by hydrothermal crystallization route. Crystallization curves were established by conducting time dependant studies on progressive crystallization processes for both the systems. The values of activation energy of nucleation (E-n), activation energy of crystallization (E-c), and their pre-exponential factors (InA(n), InA(c) respectively) were calculated from Arrhenius plots. Compared to the hydrothermal method, shorter induction period was observed when DGC method was employed. Both the E-n (49.70 kJ/mol) and E-c (52.82 kJ/mol) for DGC method were found to be lower than that of the E-n (55.70 kJ/mop and E-c (60.23 kJ/mol) for hydrothermal method. The kinetics parameters viz. K and q were derived from kinetic expressions and DGC method showed higher value of K and lower value of q compared to hydrothermal crystallization method at identical temperature. Various DGC method parameters such as water content at the bottom of autoclave and SiO2/SnO2 mole ratio have shown the influence on the kinetics of crystallization of Sn-MFI. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Crystallization; DGC; kinetics; Nucleation; Sn-MFI

Synthesis of Sn-containing anatase (TiO2) by sol-gel method and their performance in catalytic water splitting under visible light as a function of tin content - Tangale, N. P.; Niphadkar, P. S.; Samuel, V.; Deshpande, Suvarna S.; Joshi, P. N.; Awate, S. V. (Materials Letters, 2016)
Sol-gel route was employed to prepare a series of Sn-containing anatase with different molar (Ti/Sn) ratios ranging from 49 to 1. Samples were characterized by powder XRD, UV-vis, XPS, SEM, EDAX, low temperature N-2 sorption technique and Raman Spectroscopy. Except anatase phase, no other crystalline phase was observed when Ti/Sn molar ratio was varied from 49 to 9 and for Sn free sample. However, further decrease in the ratio lead to the appearance of additional SnO2 phase whose peak intensities were increased with the increase in the tin content. Irrespective of tin content, all samples showed red-shift in UV-vis spectra. Moreover, samples showed Raman shift to higher vibration side from 143 cm(-1) to 147 cm(-1) indicating the doping of Sn2+ into TiO2. By virtue of low band gap, anatase crystallite size and an absence of XRD visible SnO2, ST (19) has shown maximum photocatalytic activity upon 1 wt% Pt loading. It has exhibited the highest rate (0.1264 mmole/g/h) for visible light induced hydrogen evolution by water splitting. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Semiconductors; Sn2+ doped titania; SnO2/TiO2; Sol-gel preparation; visible light; water splitting